Kebijakan pangan di Indonesia - Maidah, Ulfa (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This article discusses the complexity of interactions between biotic and abiotic components in the environment, as well as the role of environmental science as an interdisciplinary study of the relationship between humans and the environment. The primary focus is on the concept of sustainability, which encompasses the ability of the earth’s life support system to adapt to environmental changes. Methods: This article employs a literature study approach. Finding: Sustainable development, as an effort to align economic activities with the repair of environmental damage, must uphold three main principles: solar energy, chemical cycles, and biodiversity. Additionally, the article explains the interconnection between water, energy, and food (WEF nexus) in the management of natural resources, as well as the importance of food security, which includes availability, accessibility, and utilization of food. Conclusion: The article shows that food security in Indonesia remains low, particularly in the eastern regions. Novelty/Originality of this article: This research aims to analyze the success of food security in Indonesia and contribute to more effective food security policies.